Pola Komunikasi Hubungan Jarak Jauh antara Anak dengan Orang Tua pada Siswa/Siswi SD AR Rafi Bandung - Apriliyanti Apriliyanti (Departement of Mathematics Education, 2023)
A father also makes an important contribution to a child's development, the experience experienced with a father, will influence a child into adulthood. Long-distance communication between children and parents, especially fathers, must be maintained even if they don't live in the same house. The high cost of living is one of the factors causing a father to live separately from his child to make a living. The purpose of this research is to find out the pattern of communication in long-distance relationships between children and parents, especially fathers. The theories used in this research are intrapersonal communication theory, long-distance communication theory and family communication theory. The research method used is a descriptive qualitative research method. This study seeks empirical evidence from the object of research, how to uncover patterns of distance communication relationships between children and parents in students of SD ArRafi Bandung. The results of this study indicate that ArRafi Elementary School students communicate remotely via WhatsApp, Zoom Meet and Google Meet with their father. The obstacles encountered during long-distance communication are signal interference and time constraints.